Colloidal Silicalite Coating for Improving Ionic Liquid Membrane Loading on Macroporous Ceramic Substrate for Gas Separation - Cao, Zishu; Yang, Shaowei; Sun, Xinhui; Arvanitis, Antonios; Dong, Junhang (Journal of Membrane and Separation Technology, 2016)
A thin layer of colloidal silicalite was coated on a macroporous alumina substrate to improve the effectiveness in loading and supporting ionic liquid (IL) membrane on macroporous ceramic substrate. The [bmim][BF4] IL and CO2 gas separation were used as the model system in this research. The colloidal silicalite top layer enabled the formation of a pinhole-free IL membrane with significantly reduced load of IL as compared to the bare alumina substrate because the former had a smaller and more uniform inter-particle pore size than the latter. The supported IL membrane was extensively studied for CO2 separation in conditions relevant to coal combustion flue gases. The silicalite-supported IL membrane achieved a CO2/N2 permselectivity of ~24 with CO2 permeance of ~1.0×10-8 mol/m2·s·Pa in dry conditions at 26˚C and reached a CO2/N2 separation factor of ~18 with CO2 permeance of ~1.56×10-8 mol/m2·s·Pa for a feed mixture containing ~11% CO2 and ~9% water vapor at 50oC. This supported IL membrane exhibited excellent stability under a 5-bar transmembrane pressure at 103˚C and chemical resistance to H2O, SO2, and air (O2). Results of this study also indicated that, in order to fully realize the advantages of using the colloidal silicalite support for IL membranes, it is necessary to develop macroporous ceramic supports with optimized pore size distribution so that the IL film can be retained in the micron-thin silicalite layer without penetrating into the base substrate.